Children's environmental health: an under-recognised area in paediatric health care - Sly Peter D; Pronczuk de Garbino Jenny; Gavidia Tania G (BMC, 2009)
Abstract The knowledge that the environment in which we live, grow and play, can have negative or positive impacts on our health and development is not new. However the recognition that adverse environments can significantly and specifically affect the growth and development of a child from early intrauterine life through to adolescence, as well as impact their health later in adulthood, is relatively recent and has not fully reached health care providers involved in paediatric care. Over the past 15 years, world declarations and statements on children's rights, sustainable development, chemical safety and most recently climate change, have succeeded in cultivating a global focus on children's health and their right to a healthy environment. Many international calls for research in the area, have also been able to identify patterns of environmental diseases in children, assess children's exposures to many environmental toxicants, identify developmental periods of vulnerability, and quantify the cost benefits to public health systems and beyond, of addressing environmentally related diseases in children. Transferring this information to front-line health care providers and increasing their awareness about the global burden of disease attributed to the environment and children's especial vulnerability to environmental threats is the salient aim of this commentary.